Assessment of The Millennium Development Goals (MGDs) - Salisu, Ahmed Kabiru; Batsari, Lawal Musa (NIU Journal of Social Sciences, 2020)
Millennium Development Goals, are 8 goals which the international community agreed to achieve from 2000 to 2015 that centers on eradication of extreme poverty and hunger, achieving universal primary education, promote gender equality, reducing child mortality, improving maternal health, combating HIV/AIDS, reducing prevalence of malaria, and other diseases, ensuring environmental sustainability and developing a global partnership for development. This study is an assessment of the MDGs, and the study utilized qualitative method and the data for the study was obtained from secondary source. Result from analytical analysis indicated that, while some of the goals were achieved especially in the developed countries, some other goals were not achieved mostly by the low-income countries. This paper argues that, for the world to achieve the next world development agender which is SDG, there must be more cooperation and coordination among member states in terms of resources mobilization and planning. Keywords: Millennium Development Goal, Assessment